Perspectives of Parents regarding Sexual and Reproductive Health in Early Adolescents: A Qualitative Descriptive Study - Sanghirun, Kananit; Fongkaew, Warunee; Viseskul, Nongkran; Lirtmunlikaporn, Sumalee (Pacific Rim International Journal of Nursing Research, 2020)
Families, especially parents, play an important role in promoting sexual and reproductive health among early adolescents. Thus, this qualitative descriptive study explored parents beliefs, practices and promotion of this topic with their adolescent children in urban areas of Northern Thailand. Data were collected during February 2018-February 2019 through family interviews with 28 biological parents of adolescents, aged 10-13 years, from 14 families, and analyzed using thematic analysis. Four categories emerged from data analysis. Category 1:Parental perceptions of the growing child (four sub-categories entitled Children are not ready to know about sex, Having appropriate gender roles, Sexual growth and changes in teenagers, and Focus on good genital hygiene). Category 2: Parenting practices to promote sexual health (six sub-categories: Playfully monitoring teenage friendships, Warnings about negative consequences of premarital sex, Observing changes during puberty, Advising on pubertal changes, Teaching genital hygiene practices, and Raising children to act appropriately to their gender); Category 3: Support for nurturing sexual growth (three sub-categories of adequate knowledge about sexual health, Comfort with family communication about sex, and Raising children with love and warmth); and Category 4: Constraints of raising a growing teenager (two sub-categories: Being ashamed of talking about sex, and Lack of knowledge and skills about sexual health). Our findings provide rich and essential knowledge about how to empower parents to have adequate knowledge and skills to nurture the sexual and reproductive health of their growing teenagers. Findings also contribute to enhancing the development of parental and family interventions by nurses and other health professionals, aimed at promoting sexual and reproductive health of early adolescents.